Cytological spectrum of Thyroid Lesions Using Recent Bethesda System of Reporting and its Correlation with Histomorphology: A Retrospective Study of 208 Cases in a Tertiary Care Rural Centre - Kumar Kannaujia, Sanjay; Aggarwal, Roopak; Swale, Manzeela; Ansari, Shabana A; Ansari, Azmat; Qamar, Hira (Journal of Neonatal Surgery, 2025)
Introduction : Enlargement of the thyroid gland or goiter is one of the important manifestation of thyroid lesions. It can be unilateral, bilateral or solitary nodule. It is very important to differentiate these lesions by clinical examination, thyroid function test and fine needle aspiration cytology (FNAC). It has been proved that fine needle aspiration cytology of the thyroid lesion is not only widely accepted but also simple, safe, cost effective, less painful and accurate method Material and Methods : The present study was a retrospective study conducted at Uttar Pradesh University of Medical Sciences (UPUMS), Saifai, Etawah. UPUMS is a 1500 bedded tertiary care rural hospital in north India. We collected data of 208 cases from January 2022 to June 2024 of all patients who underwent fine needle aspiration of thyroid lesions. The skin overlying the swelling was cleaned with alcohol and FNAC was done using 22-23 gauge disposable needle attached to a 10 ml plastic disposable syringe. Smears were prepared, air dried and fixe Results : The total 208 cases were archived from the Hospital Information System from January 2022 to June 2024. Out of which 24 were (11.5%) male and 184 (88.5%) were females with male to female ratio of (1:7.6 ). We reported11 cases as malignant in TBSRTC Category VI on FNAC, of which only eight cases were received for histopathological examination. We have found 100% correlation with cytological diagnosis in all the eight cases. Of these seven cases were reported as papillary carcinoma of thyroid and single case was reported as medullary carcinoma which was also confirmed by immunohistochmistry showed diffuse and strong positivity of calcitonin [Fig 13], focal weak positivity of TTF1 and negative thyroglobulin, giving the rate of malignancy 100% for this category Discussion : The malignancy rate of malignant category was observed to be 100% which is compatible with the studies conducted by Agarwal P et al [5], Arun et al [16], Williams et al [18], Mufti et al [19] and Theoharis et al [21]. While few of the studies conducted by Yang et al [22], Jo et al [20], Mondal et al [17] Nayar et al [23] and Yassa et al [6] had malignant rate between 97-99% in category VI. Conclusion : FNAC is very useful first line investigation of thyroid nodule and has been proved that it is not only widely accepted but also simple, safe, cost effective, minimally invasive, less painful and accurate method. Although it is used with success in diagnosing clear cut malignant cases but difficulty arises in follicular as well as Grey zone lesions. Hence by using TBSRTC system for reporting thyroid lesions, not only standardize the reporting but also help the clinician in planning further management of the patients.